Social and Emotional Determinants of COVID-19 Vaccination Attitudes among the Elderly at Health Center Manatuto, Timor-Leste - Chorry Santana, Aurita Dos Santos; Umbu Roga, Anderias; Weraman , Pius (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aimed to identify the key factors influencing COVID-19 vaccine acceptance among the elderly at Manatuto Villa Health Center, Kota Manatuto, Timor-Leste, with a focus on knowledge, social influence, personal experiences, emotional factors, and access to health information. A cross-sectional design was used, involving 278 respondents aged 60 years and above who completed the structured questionnaires. Data analysis was conducted using univariate, bivariate, and logistic regression to identify the main determinants of vaccine acceptance. The results revealed that 72% of respondents lacked sufficient knowledge about the benefits of COVID-19 vaccination, which was attributed to low education levels and limited access to information (p < 0.05). Additionally, 12% of the respondents reported negative experiences related to vaccine side effects, such as dizziness and nausea, which increased their hesitancy to receive subsequent doses. Social and family influences were also significant, with 71% of respondents following the advice of religious and community leaders in making vaccination decisions. Emotional factors, such as anxiety and fear of declining health due to old age, affected 67% of the respondents, becoming a barrier to vaccine acceptance. This study concludes that improving knowledge through community-based outreach programs, addressing anxiety, and involving trusted local leaders are essential strategies for enhancing vaccine acceptance among the elderly. The practical implications of these findings highlight the need for policies that focus on community education and outreach approaches to increase vaccination coverage in areas with limited access to healthcare.